Construção de edificações pré-fabricadas em Wood Frame para habitação de interesse social no Estado do Ceará: análise da viabilidade econômico-financeira, técnica e ambiental - Leite, Mariana de Araújo (2017)
Several studies point to different efficient building systems for the construction of Habitation of Social Interest (HIS), but is common to all these the construction industrialization factor. In this context, it is possible to highlight the prefabricated wood frame system, object of study of the research in question, a solution that is adequate to the construction demand for HIS due to several reasons, such as those related to productivity, quality, speed, gaining prominence by the sustainable factor. This system is a constructive solution still relatively new in Brazil, although it is not a novelty to the world. It has not yet gained space in all Brazilian states, being concentrated in the south and southeast regions of the country, where the pre-fabrication factories of wood frame panels are located. Thus, the research aims to analyze the economic-financial, technical and environmental feasibility and the implications of the use of the prefabricated wood frame construction system in the construction of Habitation of Social Interest (HIS) in the State of Ceará. For this, initially technical visits were made in Brazilian companies that representing all stages of the cycle of production of buildings in wood frame system. From these visits, technical factors of greater prominence and questions about the environmental impacts of the system were analyzed, seeking to adapt to the reality of the Ceará State, aiming the analysis of technical and environmental feasibility. As a continuity, hypothetical scenarios were elaborated to analyze the costs of the implementation of this system in the State of Ceará, seeking to analyze the economic-financial feasibility. In addition to the national scope, it was sought to observe some international practices, references in the subject, in order to compare with Brazilian production, aiming a more realistic characterization, addressing perceived advantages and limitations. The results indicated that it is feasible, within the studied aspects, the implantation of the wood frame system in Ceará for the HIS typology, obeying the limitations established in the work. Also indicate that there is a need for wider dissemination of the system, its characteristics and possibilities of use, so that the knowledge manages in the construction professionals and the general population increased interest and confidence, making the wood frame is a real possibility for all the Brazilian regions. It is concluded that this is an initial work since in the State of Ceará is the first study on the subject, which provides the possibility of being continued, improved and developed from other strands and visions of other authors.